IKLIM ORGANISASI DINAS PENDIDIKAN, PEMUDA DAN OLAHRAGA KOTA SAWAHLUNTO - Kasmawarita , (Jurnal Bahana Manajemen Pendidikan, 2014)
This study is based on observations of the author at the Department of Education, Youth and Sports Sawahlunto that organizational climate of Education, Youth and Sports Sawahlunto not reflect a conducive organizational climate. The purpose of this study was to obtain an overview of the organizational climate from the aspects: freedom, confidence, warmth, and responsibilities of Education, Youth and Sports Sawahlunto.The study population was all employees of the Department of Education, Youth and Sports Sawahlunto as many as 44 people. Means of data collection in this study was a questionnaire, which is arranged in the form of a Likert scale that has been in the validity and realibilitasnya. Data were analyzed by using the formula average (mean).The results showed that: the freedom, confidence, warmth and responsibilities conducive with a score of: 3.5, 3.3, 3.6 and 3.4. Thus it can be said that the organizational climate of Education, Youth and Sports Sawahlunto that in view of the aspects of freedom, confidence, warmth, employee responsibilities quite conducive. Keywords: ClimateOrganization